2021
DOI: 10.3390/ma14092172
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Induced Transparency in Media with Helical Dichroic Structure

Abstract: In our paper, the magneto-optical properties of a dichroic cholesteric liquid crystal layer with large values of magneto-optical parameter g and low values of dielectric permittivity were investigated. The solutions of the dispersion equation and their peculiarities were investigated in detail. The specific properties of reflection, transmission, absorption, rotation, ellipticity spectra and also the spectra of ellipticity and azimuth of eigen polarization were investigated. The existence of a tunable linear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Consideration of this limiting case, below, will allow us to reveal many features of magnetooptical CLCs in their purest form, which in the more general case of Re∆≠ 0 have more complex manifestations. Some features of the optical properties of such media are considered in detail in [33][34][35]. In this case Eq.…”
Section: Models and Methodology Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consideration of this limiting case, below, will allow us to reveal many features of magnetooptical CLCs in their purest form, which in the more general case of Re∆≠ 0 have more complex manifestations. Some features of the optical properties of such media are considered in detail in [33][34][35]. In this case Eq.…”
Section: Models and Methodology Resultsmentioning
confidence: 99%
“…The papers [16][17][18][19][20][21][22][23][24][25][26] present the results of a theoretical and experimental study of the magnetooptical properties of CLCs. Then, in the papers [27][28][29][30] the existence of MIT and MIA was demonstrated in short wavelength part of spectrum in CLCs being in external magnetic field both at the presence and absence of local dielectric anisotropy. In [31] it was reported about observation of Dirac points in CLCs, both in the presence of external magnetic field and in its absence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the papers [41][42][43][44][45][46][47][48][49][50] the results of a theoretical and experimental study of the magneto-optical properties of CLCs are presented. Moreover, in the papers [51][52][53][54] the existence of MIT and MIA was demonstrated. In [55] it was reported about observation of Dirac points in CLCs.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the MIT and MIA phenomena are observed near the Dirac points. Let us note, that all the works [51][52][53][54][55] deal with the case when the parameter of magneto-optical activity g is constant and is independent of wavelength. In this paper, we will discuss the possibility of observing Dirac points and lines and exceptional points and lines in magnetically active CLCs in the case when the parameter of magneto-optical activity g is function of wavelength.…”
Section: Introductionmentioning
confidence: 99%